CO2 Reforming of Methane over Ni/Ce-SBA-15: Effects of Ce Addition - Nurul Aini, Razali; Nurul Ainun Nabihah, AbGhazab; Setiabudi, H. D.; Chin, S. Y. (Informatics Publishing Limited, 2017)
Background/Objectives: The effects of Ce loading (1-7 wt%) on the properties of Ni/SBA-15 andCO2 dry reforming with methane was studied. Methods/StatisticalAnalysis: The physicochemical properties of the catalysts were analyzed by XRD, BET, TEM and FTIR. Catalytic performance of catalyst was performed using a fixed bed reactor at 700°C. Findings: NCS7 catalyst had the highest activity and good stability with CH4 conversion, CO2 conversion and H2/CO ratio of 94.9%, 95.1%, and 0.99, respectively. This can be attributed to the Ce ensuring a good Ni dispersion and inhibited the carbon deposition on the catalyst surfaces. Moreover, high Ce loading of NCS7 promoting the formation of a significant synergy effect between Ni active sites with SBA-15 for target reaction. Application/Improvements: The result presented is very promising to improve the GHGs conversion strategies for the production of useful chemical products.